Offshore photovoltaic cable material and preparation method and application thereof
By designing and preparing raw materials, a specific three-dimensional crosslinking network structure is formed, which solves the problem that existing offshore photovoltaic cable materials cannot meet the high standard requirements under harsh conditions at sea, and achieves the excellent mechanical properties and weather resistance of the materials.
Patent Information
- Application Number
- CN202411726623.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-11
AI Technical Summary
Existing offshore photovoltaic cable materials cannot effectively meet the high standards under harsh conditions at sea, including heat resistance, moisture resistance, UV aging resistance, corrosion resistance and mildew resistance.
By designing and combining raw materials, a dense and stable crosslinking system is formed, using polyethylene, ethylene-octene copolymer, butadiene-based polymer, accretive crosslinking agent and alkenyl oligosilsesquioxane, etc. Components form a specific three-dimensional crosslinking network structure.
It has achieved excellent mechanical properties, heat resistance, salt spray resistance, moisture and heat resistance, flame retardancy, mildew resistance and weather resistance of offshore photovoltaic cable materials, and met the needs of long-term and stable operation under harsh conditions at sea.
Smart Images

Figure BDA0005159357560000021 
Figure BDA0005159357560000031 
Figure BDA0005159357560000061
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of cable materials, and in particular relates to an offshore photovoltaic cable material and a preparation method and application thereof. Background Art
[0002] Offshore photovoltaics is an emerging clean energy technology with huge development potential, and has gradually attracted widespread attention in the industry. On the one hand, the ocean covers more than 70% of the earth's surface and has abundant solar energy resources. On the other hand, offshore photovoltaic projects can make full use of the advantages of the marine environment, such as open sea surface, no obstructions, long sunshine hours, etc., to improve the efficiency of photovoltaic power generation. Cables are energy transmission elements in photovoltaic power generation systems and play a key role in offshore photovoltaic power generation components. The development of cable materials is of great significance to the stable operation of photovoltaic power generation systems and the rapid development of green energy.
[0003] CN106898427A discloses a cable for an offshore photovoltaic power station, which is composed of a plurality of conductor monofilaments twisted into a conductor, a water-blocking tape wrapped around the conductor to form a cable core, a water-blocking swelling paste is filled between the conductors and between the conductor and the water-blocking tape, a radiation-crosslinked polyolefin insulation layer is extruded outside the cable core, and a radiation-crosslinked polyolefin outer sheath is extruded outside the insulation layer. The cable has good UV resistance, high temperature resistance, corrosion resistance and water-blocking properties to adapt to different working environments in offshore photovoltaic power stations.
[0004] CN117777586A discloses a sheath material for offshore photovoltaic cables, the raw material components are as follows: 5-15 parts of maleic anhydride grafted EPDM rubber, 13-22 parts of ethylene-octene copolymer, 10-20 parts of ethylene-vinyl acetate copolymer, 45-65 parts of flame retardant, 5-10 parts of synergistic flame retardant, 0.5-2 parts of antioxidant, 1-3 parts of lubricant, 1-2 parts of silane coupling agent, 0.5-1.5 parts of multifunctional cross-linking agent, 0.5-1.2 parts of mildewproof agent, and 0.8-1.5 parts of graphene. The sheath material is obtained by cross-linking through electron accelerator irradiation, and has good performance in salt spray resistance, mildew resistance, mechanical properties, flame retardancy, heat resistance, and aging resistance.
[0005] CN102964668A discloses a chemically cross-linked polyolefin insulating rubber for offshore oil and gas engineering cables. The raw materials for preparing the chemically cross-linked polyolefin insulating rubber include ethylene-vinyl acetate copolymer, high-density polyethylene, ethylene-methacrylic acid copolymer, cross-linking agent DCP, antioxidant 1076, antioxidant DNP, stearic acid, aluminum hydroxide, red phosphorus and ultraviolet absorber UV-326. The insulating rubber has a high heat resistance grade and has good ultraviolet resistance, seawater moisture erosion resistance and oil aging resistance.
[0006] Although there is no shortage of offshore cable material development in the industry, offshore photovoltaic cables need to be able to withstand harsh conditions such as high salt, high humidity, high temperature and exposure in the marine environment, which requires cable materials to have outstanding corrosion resistance, heat resistance, moisture resistance, UV aging resistance and mildew resistance. Current cable materials cannot meet the high standards of offshore photovoltaic cables. Therefore, the development of an offshore photovoltaic cable material with excellent heat resistance, moisture resistance, UV aging resistance, corrosion resistance and mildew resistance is an urgent problem to be solved in this field. Summary of the invention
[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an offshore photovoltaic cable material and a preparation method and application thereof. Through the design and compounding of each component, a dense and stable cross-linking system can be formed, so that the offshore photovoltaic cable material has excellent heat resistance, moisture and heat resistance, UV aging resistance and salt spray corrosion resistance, as well as excellent flame retardancy and mildew resistance, which can fully meet the needs of long-term stable operation under harsh conditions at sea.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides an offshore photovoltaic cable material, wherein the raw materials for preparing the offshore photovoltaic cable material include the following components in parts by mass:
[0010]
[0011]
[0012] In the preparation raw materials of the present invention, polyethylene is used as a matrix, and ethylene-octene copolymer, butadiene-based polymer, and co-crosslinking agent are used. Under the action of an initiator, a specific crosslinking network can be formed through a free radical mechanism crosslinking reaction to obtain a high degree of crosslinking, and the mechanical properties, heat resistance, and salt spray corrosion resistance of the cable material are synergistically improved. The alkenyl-containing oligomeric silsesquioxane contains a Si-O-Si skeleton structure, which has heat insulation and flame retardant properties on the one hand, and can synergistically exert a flame retardant effect with the flame retardant; on the other hand, it contains an alkenyl functional group, which can react chemically with an organic system (including butadiene-based polymers, co-crosslinking agents, ethylene-octene copolymers, polyethylene, etc.), and embed the Si-O-Si skeleton structure into the crosslinking network of the polymer, further improving the mechanical properties, heat stability, and salt spray resistance of the cable material, while being able to block water vapor intrusion and improve the moisture resistance and wet heat resistance of the cable material. The present invention forms a specific three-dimensional cross-linked network structure in the cable material through the design and mutual compounding of components, so that the offshore photovoltaic cable material has excellent mechanical properties, heat resistance, salt spray resistance and moisture and heat resistance, and also has excellent performance in flame retardancy, mildew resistance, weather resistance and UV aging resistance, and can fully meet the needs of long-term stable operation under harsh conditions at sea.
[0013] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0014] In the raw materials for preparing the offshore photovoltaic cable material of the present invention, the mass proportion of the polyethylene is 60-80 parts, for example, it can be 62 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts or 78 parts, as well as specific point values between the above point values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0015] The mass parts of the ethylene-octene copolymer are 5-20 parts, for example, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 15 parts, 16 parts or 18 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0016] The mass parts of the butadiene-based polymer are 5-20 parts, for example, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 15 parts, 16 parts or 18 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0017] The mass fraction of the alkenyl-containing oligomeric silsesquioxane is 2-10 parts, for example, it can be 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0018] The mass fraction of the initiator is 0.1-4 parts, for example, it can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts or 3.8 parts, as well as specific point values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0019] The weight percentage of the auxiliary cross-linking agent is 0.1-4 parts, for example, it can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts or 3.8 parts, as well as specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0020] The mass parts of the flame retardant are 40-100 parts, for example, it can be 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts or 95 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0021] The mass fraction of the mildew inhibitor is 0.1-5 parts, for example, it can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0022] Preferably, the polyethylene includes any one of linear low-density polyethylene, high-density polyethylene, and metallocene polyethylene, or a combination of at least two thereof, and more preferably a combination of high-density polyethylene (HDPE) and metallocene polyethylene.
[0023] As a preferred technical solution of the present invention, the polyethylene includes a combination of HDPE and metallocene polyethylene, HDPE has excellent hardness, tensile strength, toughness and creep, and high chemical stability, and metallocene polyethylene is a linear polyethylene prepared by catalysis using a metallocene (MAO) catalyst, and has a narrow molecular weight distribution, a regular molecular chain structure, good processing performance, and a large elongation at break. The combination of HDPE and metallocene polyethylene as a polyethylene matrix can improve the mechanical properties and processing properties of the offshore photovoltaic cable material.
[0024] Preferably, the mass ratio of the high-density polyethylene to the metallocene polyethylene is (1-5):1, for example, it can be 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1 or 4.5:1, etc.
[0025] Preferably, the melt index of the metallocene polyethylene at 190°C and 2.16kg is 0.02-10g / 10min, for example, it can be 0.1g / 10min, 0.3g / 10min, 0.5g / 10min, 0.8g / 10min, 1g / 10min, 1.5g / 10min, 2g / 10min, 2.5g / 10min, 3g / 10min, 3.5g / 10min, 4g / 10min, 4.5g / 10min, 5g / 10min, 6g / 10min, 7g / 10min, 8g / 10min or 9g / 10min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 0.05-5.5g / 10min is further preferred.
[0026] Preferably, the melt index of the ethylene-octene copolymer at 190°C and 2.16kg is 1-20g / 10min, for example, 2g / 10min, 3g / 10min, 4g / 10min, 5g / 10min, 6g / 10min, 7g / 10min, 8g / 10min, 9g / 10min, 10g / 10min, 12g / 10min, 14g / 10min, 15g / 10min, 16g / 10min or 18g / 10min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific point values included in the range, and 1.2-8g / 10min is further preferred.
[0027] Preferably, the butadiene-based polymer includes any one of polybutadiene and butadiene-styrene copolymer, or a combination of at least two thereof.
[0028] Preferably, the butadiene-based polymer comprises a structural unit represented by formula I, and the molar percentage of the structural unit represented by formula I in the butadiene-based polymer is 20-90%, for example, it can be 25%, 30%, 35%, 40%, 45%, 50%, 52%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 88%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 50-90% is further preferred.
[0029]
[0030] In the present invention, the butadiene-based polymer contains a specific proportion of 1,2-vinyl structural units shown in formula I, and the vinyl in the side chain has a high reactivity, and can undergo a free radical mechanism cross-linking reaction with a co-crosslinking agent, ethylene-octene copolymer, polyethylene, and alkenyl-containing oligomeric silsesquioxane in the presence of an initiator, forming a specific three-dimensional cross-linked network structure in the cable material, thereby giving the offshore photovoltaic cable material excellent mechanical properties, heat aging resistance, salt spray resistance, and wet heat resistance. If the 1,2-vinyl structural unit shown in formula I is not contained or its content is too low, the cross-linking degree will be reduced, resulting in a decrease in the heat aging resistance and salt spray corrosion resistance of the cable material.
[0031] Preferably, the number average molecular weight of the butadiene-based polymer is 1000-10000, for example, it may be 2000, 3000, 4000, 5000, 6000, 7000, 8000 or 9000, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0032] Preferably, the mass ratio of the butadiene-based polymer to the ethylene-octene copolymer is (1.2-2.5):1, for example, it can be 1.4:1, 1.5:1, 1.6:1, 1.8:1, 2:1, 2.2:1 or 2.4:1, etc.
[0033] In the present invention, the ethylene-octene copolymer (POE) has excellent flexibility, viscoelasticity and processing performance, and the butadiene-based polymer can provide abundant chemical crosslinking sites, which is helpful to improve the aging resistance and corrosion resistance of the cable material; by controlling the mass ratio of the butadiene-based polymer to the ethylene-octene copolymer to be (1.2-2.5): 1, the offshore photovoltaic cable material can achieve an excellent balance effect between processing performance, mechanical properties, heat aging resistance, salt spray corrosion resistance and weather resistance. If the mass ratio of the two exceeds the aforementioned range, it will affect the performance balance of the cable material. Too much POE will reduce the heat resistance and salt spray corrosion resistance to a certain extent, while too much butadiene-based polymer will affect the elongation at break and processing performance of the cable material.
[0034] Preferably, the alkenyl-containing oligomeric silsesquioxane has a polyhedral structure, and is preferably an alkenyl-containing cage-shaped oligomeric silsesquioxane.
[0035] Preferably, the alkenyl-containing oligomeric silsesquioxane includes any one of octavinyl cage-type oligomeric silsesquioxane, octamethacrylate cage-type oligomeric silsesquioxane, octaacrylate cage-type oligomeric silsesquioxane, octaacryloxy cage-type oligomeric silsesquioxane, octamethacryloxy cage-type oligomeric silsesquioxane, and methacryloxypropyl cage-type polysilsesquioxane, or a combination of at least two thereof.
[0036] Preferably, the initiator comprises an organic peroxide, further preferably any one or a combination of at least two of cumene hydroperoxide, di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, dibenzoyl peroxide, cyclohexanone peroxide, tert-butyl perbenzoate, tert-butyl peracetate, tert-amyl peroxy (2-ethylhexyl) carbonate, di(4-methylbenzoyl) peroxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide ethane, and tert-butyl peroxy-3,5,5-trimethylhexanoate.
[0037] Preferably, the auxiliary cross-linking agent is a compound containing at least 2 (≥2, such as 2, 3, 4, 5, 6, etc.) unsaturated groups (such as alkenyl groups).
[0038] Preferably, the auxiliary cross-linking agent includes any one of triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, tri(1,2-propylene glycol) diacrylate, tri(2-hydroxyethyl)isocyanuric acid triacrylate, propoxylated trimethylolpropane triacrylate, or a combination of at least two thereof;
[0039] Preferably, the flame retardant includes any one of antimony trioxide, aluminum hydroxide, and magnesium hydroxide, or a combination of at least two of them.
[0040] The present invention does not specifically limit the type of mildew inhibitor, and the present invention is applicable to any mildew inhibitor known in the prior art that can be used for cable materials.
[0041] Preferably, the mildew preventer includes any one of an organic mildew preventer, an inorganic mildew preventer, and a natural extract mildew preventer, or a combination of at least two of them.
[0042] Preferably, the preparation raw materials further include any one of a compatibilizer, a stabilizer, a lubricant, a silane coupling agent, an ultraviolet absorber, and an antioxidant, or a combination of at least two thereof.
[0043] Preferably, the preparation raw materials also include 1-10 parts of compatibilizer in parts by mass, and the mass parts of the compatibilizer can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0044] Preferably, the compatibilizer includes any one of maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, and maleic anhydride grafted ethylene-vinyl acetate copolymer, or a combination of at least two thereof.
[0045] Preferably, the preparation raw materials also include 0.1-5 parts of stabilizer by mass, and the mass parts of the stabilizer can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0046] Preferably, the stabilizer includes any one of calcium stearate, zinc stearate, and pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) or a combination of at least two thereof.
[0047] Preferably, the preparation raw material also includes 0.1-5 parts of lubricant by mass, and the mass parts of the lubricant can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0048] Preferably, the lubricant includes any one of silicone masterbatch, silicone phenol, polyethylene wax, or a combination of at least two thereof.
[0049] Preferably, the preparation raw materials further include 0.1-5 parts of a silane coupling agent by mass, and the mass parts of the silane coupling agent can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0050] Preferably, the silane coupling agent includes any one of a vinyl silane coupling agent, an epoxy silane coupling agent, an amino silane coupling agent, and a mercapto silane coupling agent, or a combination of at least two thereof.
[0051] Preferably, the silane coupling agent includes any one of vinyltriethoxysilane, vinyltrimethoxysilane, methacryloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloxy)propyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and γ-aminoethylaminopropyltrimethoxysilane, or a combination of at least two thereof.
[0052] Preferably, the preparation raw materials further include 0.1-3 parts of ultraviolet absorbers by mass, and the mass parts of the ultraviolet absorbers can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts or 2.8 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0053] Preferably, the ultraviolet absorber includes any one of benzotriazole additives, salicylate additives, benzophenone additives, substituted acrylonitrile additives, triazine additives, and hindered amine additives, or a combination of at least two thereof.
[0054] In a second aspect, the present invention provides a method for preparing the offshore photovoltaic cable material as described in the first aspect, the preparation method comprising:
[0055] The prepared raw materials are mixed and extruded to obtain pellets;
[0056] The granules are made into wires through a wire extruder, and the wires are irradiated and cross-linked through an electron accelerator to obtain the offshore photovoltaic cable material.
[0057] The preparation method of the offshore photovoltaic cable material provided by the present invention includes two cross-linking processes. The first cross-linking is heat-induced cross-linking, which mainly occurs during the mixing process, so that the obtained granules contain a certain cross-linked grid structure; further, after the granules are processed into wires, they are irradiated and cross-linked by an electron accelerator, so that the organic system undergoes secondary cross-linking to obtain a specific multi-dimensional cross-linked network structure, thereby giving the offshore photovoltaic cable material excellent mechanical properties, heat resistance, salt spray resistance, moisture and heat resistance, weather resistance and UV aging resistance.
[0058] Preferably, the mixing is carried out in an internal mixer.
[0059] Preferably, the mixing temperature is 160-175°C, for example, it can be 162°C, 165°C, 168°C, 170°C, 172°C or 174°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0060] Preferably, the mixing time is 5-30 min, for example, it can be 6 min, 8 min, 10 min, 12 min, 15 min, 18 min, 20 min, 22 min, 25 min or 28 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0061] Preferably, the extrusion granulation is carried out in a screw extruder, such as a single-screw extruder or a twin-screw extruder.
[0062] Preferably, the operating temperature of the screw extruder is 100-150°C, for example, it can be 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C or 145°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 110-130°C is further preferred.
[0063] Preferably, the screw extruder comprises a first zone, a second zone, a third zone, a fourth zone, a fifth zone, a sixth zone and a seventh zone connected in sequence, and the temperature of each zone is independently 110-130°C, for example, it can be 112°C, 115°C, 118°C, 120°C, 122°C, 125°C or 128°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0064] Preferably, the temperature of the first zone in the screw extruder is 110-115°C (e.g., 110°C, 111°C, 112°C, 113°C, 114°C or 115°C, etc.), the temperature of the second zone is 115-120°C (e.g., 115°C, 116°C, 117°C, 118°C, 119°C or 120°C, etc.), the temperature of the third zone is 115-120°C (e.g., 115°C, 116°C, 117°C, 118°C, 119°C or 120°C, etc.), and the temperature of the fourth zone is 120-125°C (e.g., 1 The temperature of the fifth zone is 120-125°C (for example, 120°C, 121°C, 122°C, 123°C, 124°C or 125°C, etc.), the temperature of the sixth zone is 120-130°C (for example, 120°C, 122°C, 124°C, 126°C, 128°C or 130°C, etc.), and the temperature of the seventh zone is 125-130°C (for example, 125°C, 126°C, 127°C, 128°C, 129°C or 130°C, etc.).
[0065] Preferably, the operating temperature of the wire extruder is 100-190°C, for example, it can be 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0066] Preferably, the wire extruder comprises a zone A, a zone B, a zone C and a zone D connected in sequence, so that the pellets can pass through zones A, B, C and D in sequence, wherein the operating temperature of zone A is 150-160°C (e.g., 152°C, 154°C, 155°C, 158°C, 159°C, etc.), the operating temperature of zone B is 165-175°C (e.g., 166°C, 168°C, 170°C, 172°C, 174°C, etc.), the operating temperature of zone C is 165-175°C (e.g., 166°C, 168°C, 170°C, 172°C, 174°C, etc.), and the operating temperature of zone D is 170-180°C (e.g., 172°C, 174°C, 175°C, 176°C, 178°C, etc.).
[0067] Preferably, the dose of the radiation cross-linking is 4-10 Mrad, for example, it can be 4.5 Mrad, 5 Mrad, 5.5 Mrad, 6 Mrad, 6.5 Mrad, 7 Mrad, 7.5 Mrad, 8 Mrad, 8.5 Mrad, 9 Mrad or 9.5 Mrad, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0068] In a third aspect, the present invention provides a use of the offshore photovoltaic cable material as described in the first aspect in an offshore photovoltaic module.
[0069] Compared with the prior art, the present invention has the following beneficial effects:
[0070] (1) In the offshore photovoltaic cable material provided by the present invention, the components are designed and compounded to cooperate with each other to form a cross-linking system jointly constructed by polyethylene, ethylene-octene copolymer, butadiene-based polymer, co-crosslinking agent and alkenyl-containing oligomeric silsesquioxane, so as to form a specific three-dimensional cross-linked network structure in the cable material, so that the offshore photovoltaic cable material has excellent mechanical properties, heat resistance, salt spray resistance and moisture and heat resistance, and also has excellent performance in flame retardancy, mildew resistance, weather resistance and UV aging resistance.
[0071] (2) Through the design and further optimization of the components, the present invention makes the tensile strength of the offshore photovoltaic cable material ≥15.5MPa, the elongation at break ≥320%, the change rate of tensile strength and the change rate of elongation at break after aging at 150°C for 168h ≤±5%, the tensile strength retention rate after double 85 test for 168h ≥88%, the change rate of tensile strength and the change rate of elongation at break after 30 days of salt spray test ≤±10%, and can pass the single vertical burning and mildew resistance test, and has excellent comprehensive performance in mechanical properties, heat resistance, salt spray resistance, moisture and heat resistance, flame retardancy, mildew resistance, etc., fully meeting the needs of long-term stable operation under harsh conditions at sea. DETAILED DESCRIPTION
[0072] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0073] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0074] "Optionally", "optionally" or "either" means that the subsequently described matter or event can or cannot occur, and that the description includes cases where the event occurs and cases where it does not.
[0075] In the following specific implementation of the present invention, the specific information of the materials used is as follows:
[0076]
[0077]
[0078] The offshore photovoltaic cable material and the preparation method thereof according to the present invention will be described in detail below by taking a plurality of embodiments as examples, but the offshore photovoltaic cable material and the preparation method thereof according to the present invention are not limited to these embodiments.
[0079] Example 1
[0080] An offshore photovoltaic cable material, the raw materials for its preparation include the following components in parts by mass:
[0081]
[0082]
[0083] The preparation method of the offshore photovoltaic cable material is as follows:
[0084] (1) adding each component into a mixer according to the formula amount, premixing for 3 minutes to obtain a mixture; adding the mixture into an internal mixer, mixing at 170° C. for 20 minutes, and extruding and granulating through a single screw extruder to obtain pellets; the operating temperatures of zones 1 to 7 in the single screw extruder are 112° C., 115° C., 115° C., 120° C., 120° C., and 125° C., respectively.
[0085] (2) adding the pellets obtained in step (1) into a wire extruder and extruding to obtain wires, wherein the operating temperatures of the AD zone in the wire extruder are 155° C., 170° C., 170° C., and 175° C., respectively; irradiating the wires with an electron accelerator for cross-linking, and the irradiation dose is 5 Mrad to obtain the offshore photovoltaic cable material.
[0086] The following performance tests are conducted on offshore photovoltaic cable materials:
[0087] (1) Tensile strength and elongation at break: tested according to the method in GB / T 2951.11-2008;
[0088] (2) Heat resistance: After the cable material to be tested is aged at 150°C for 168 hours, the tensile strength (tensile strength) and elongation at break are tested and compared with the data measured in (1) to obtain the change rate; change rate = (test value after aging - original test value) / original test value; the smaller the absolute value of the change rate, the better the heat resistance.
[0089] (3) Moisture and heat resistance: The cable material to be tested is placed in a moisture and heat aging test chamber at 85°C and 85% humidity. After 168 hours, the tensile strength is tested and compared with the data measured in (1) to obtain the tensile strength retention rate; tensile strength retention rate = test value after aging / original test value. The higher the retention rate, the better the moisture and heat resistance.
[0090] (4) Salt spray corrosion resistance: A cyclic corrosion test was performed according to the method in IEC 60068-2-52. After 30 days, the tensile strength and elongation at break were tested and compared with the data measured in (1) to obtain the rate of change. The smaller the absolute value of the rate of change, the better the salt spray corrosion resistance.
[0091] (5) Single vertical burning: Tested according to the method in GB / T 18380-2008;
[0092] (6) Mildew resistance: tested according to the method in standard GB / T 2423.16-2008;
[0093] The test results are shown in Table 1.
[0094] Examples 2-8, Comparative Examples 1-4
[0095] A marine photovoltaic cable material, which differs from Example 1 only in that the type and / or amount of raw materials used in the preparation are different, as shown in Tables 1 and 2, wherein "--" represents that the component is not added; the preparation method of the marine photovoltaic cable material is the same as that in Example 1; the performance of the marine photovoltaic cable material is tested by the same method as in Example 1, and the test data are shown in Tables 1 and 2.
[0096] Table 1
[0097]
[0098]
[0099]
[0100] Table 2
[0101]
[0102]
[0103] According to the performance test data in Table 1, the present invention forms a three-dimensional cross-linked network of a specific structure in the cable material by designing and compounding the components in the raw materials, so that the offshore photovoltaic cable material has excellent mechanical properties, heat resistance, salt spray resistance, moisture and heat resistance, flame retardancy, mildew resistance and weather resistance; wherein, the tensile strength of Examples 1-5 is 15.6-16.3MPa, the elongation at break is 322-340%, the tensile change rate and the elongation at break after aging at 150°C for 168h are ≤±5%, the tensile change rate and the elongation at break after 30 days of salt spray resistance test are ≤±10%, the tensile strength retention rate after 168h of double 85 test is 89-92%, and it can pass the single vertical burning and mildew resistance test, and has achieved significant improvement in heat aging resistance, salt corrosion resistance and moisture and heat resistance.
[0104] Further, in combination with the effect data of Example 1 and Examples 6-8, it can be seen that the present invention can regulate the cross-linked network structure in the cable material and synergistically improve the mechanical properties, heat aging resistance and salt spray corrosion resistance of the cable material by designing the content of 1,2-vinyl structural units in the butadiene-based polymer and designing and optimizing the dosage of the butadiene-based polymer and POE. The 1,2-vinyl structural unit content of the butadiene-based polymer in Example 6 is relatively low, resulting in a decrease in the cross-linking density, which affects the mechanical properties, heat aging resistance and salt spray corrosion resistance of the cable material. The dosage ratio of the butadiene-based polymer to POE in Examples 7-8 exceeds the preferred (1.2-2.5): 1 of the present invention, resulting in varying degrees of decrease in the mechanical properties, heat aging resistance and salt spray corrosion resistance of the material.
[0105] The present invention forms a cross-linking system composed of polyethylene, ethylene-octene copolymer, butadiene-based polymer, co-crosslinking agent and alkenyl-containing oligomeric silsesquioxane in the cable material by designing and compounding each component in the raw material preparation. Based on the formation of a three-dimensional cross-linking network with a specific structure, the offshore photovoltaic cable material achieves an excellent balance between processing performance, mechanical properties, heat aging resistance, salt spray corrosion resistance, moisture and heat resistance and weather resistance. Comparative Example 1 does not contain a butadiene-based polymer, and Comparative Example 2 contains hydrogenated SEBS, which cannot provide reactive side chain alkenyl groups, resulting in insufficient cross-linking of the cable material, resulting in a significant decrease in its tensile strength, elongation, heat aging resistance, salt spray corrosion resistance and moisture and heat resistance. The oligomeric silsesquioxane in Comparative Example 3 does not contain a double bond functional group, and the oligomeric silsesquioxane is only blended in the cable material as a filler, which affects the mechanical properties and aging resistance of the cable material. Comparative Example 4 does not contain an initiator, and the material is difficult to undergo heat-induced cross-linking reaction during the mixing stage. The cross-linked structure obtained by radiation cross-linking alone is not dense and stable enough, resulting in a comprehensive deterioration of the mechanical properties, heat aging resistance, salt spray corrosion resistance and moisture and heat resistance of the cable material.
[0106] The applicant declares that the present invention illustrates the offshore photovoltaic cable material and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. An offshore photovoltaic cable material, characterized in that: The raw materials for preparing the offshore photovoltaic cable material include the following components by mass:
2. The offshore photovoltaic cable material according to claim 1, characterized in that: The polyethylene includes any one of linear low-density polyethylene, high-density polyethylene, and metallocene polyethylene, or a combination of at least two thereof, preferably a combination of high-density polyethylene and metallocene polyethylene; Preferably, the mass ratio of the high-density polyethylene to the metallocene polyethylene is (1-5):1; Preferably, the melt index of the ethylene-octene copolymer at 190° C. and 2.16 kg is 1-20 g / 10 min.
3. The offshore photovoltaic cable material according to claim 1 or 2, characterized in that: The butadiene-based polymer includes any one of polybutadiene and butadiene-styrene copolymer or a combination of at least two thereof; Preferably, the butadiene-based polymer comprises a structural unit represented by formula I, and the molar percentage of the structural unit represented by formula I in the butadiene-based polymer is 20-90%; Preferably, the number average molecular weight of the butadiene-based polymer is 1000-10000; Preferably, the mass ratio of the butadiene-based polymer to the ethylene-octene copolymer is (1.2-2.5):
1.
4. The offshore photovoltaic cable material according to any one of claims 1 to 3, characterized in that: The alkenyl-containing oligomeric silsesquioxane includes any one of octavinyl cage-type oligomeric silsesquioxane, octamethacrylate cage-type oligomeric silsesquioxane, octaacrylate cage-type oligomeric silsesquioxane, octaacryloxy cage-type oligomeric silsesquioxane, octamethacryloxy cage-type oligomeric silsesquioxane, and methacryloxypropyl cage-type polysilsesquioxane, or a combination of at least two thereof.
5. The offshore photovoltaic cable material according to any one of claims 1 to 4, characterized in that: The initiator comprises an organic peroxide, preferably any one or a combination of at least two of cumene hydroperoxide, di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, dibenzoyl peroxide, cyclohexanone peroxide, tert-butyl perbenzoate, tert-butyl peracetate, tert-amyl peroxy (2-ethylhexyl) carbonate, di(4-methylbenzoyl) peroxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide ethane, and tert-butyl peroxy-3,5,5-trimethylhexanoate; Preferably, the auxiliary cross-linking agent includes any one of triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, tri(1,2-propylene glycol) diacrylate, tri(2-hydroxyethyl)isocyanuric acid triacrylate, propoxylated trimethylolpropane triacrylate, or a combination of at least two thereof; Preferably, the flame retardant includes any one of antimony trioxide, aluminum hydroxide, and magnesium hydroxide, or a combination of at least two of them.
6. The offshore photovoltaic cable material according to any one of claims 1 to 5, characterized in that: The preparation raw materials also include any one or a combination of at least two of a compatibilizer, a stabilizer, a lubricant, a silane coupling agent, an ultraviolet absorber, and an antioxidant; Preferably, the preparation raw material further comprises 1-10 parts by mass of a compatibilizer; Preferably, the compatibilizer includes any one of maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, and maleic anhydride grafted ethylene-vinyl acetate copolymer, or a combination of at least two thereof; Preferably, the raw material for preparation further comprises 0.1-5 parts of a stabilizer by weight; Preferably, the stabilizer includes any one of calcium stearate, zinc stearate, and pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) or a combination of at least two thereof; Preferably, the raw material for preparation further comprises 0.1-5 parts by mass of a lubricant; Preferably, the lubricant comprises any one of silicone masterbatch, silicone phenol, polyethylene wax, or a combination of at least two thereof; Preferably, the raw material for preparation further comprises 0.1-5 parts by mass of a silane coupling agent; Preferably, the silane coupling agent includes any one of a vinyl silane coupling agent, an epoxy silane coupling agent, an amino silane coupling agent, and a mercapto silane coupling agent, or a combination of at least two thereof; Preferably, the raw material for preparation further comprises 0.1-3 parts by mass of ultraviolet absorber.
7. A method for preparing an offshore photovoltaic cable material according to any one of claims 1 to 6, characterized in that: The preparation method comprises: The prepared raw materials are mixed and extruded to obtain pellets; The granules are made into wires through a wire extruder, and the wires are irradiated and cross-linked through an electron accelerator to obtain the offshore photovoltaic cable material.
8. The preparation method according to claim 7, characterized in that: The mixing is carried out in an internal mixer; Preferably, the mixing temperature is 160-175°C and the mixing time is 5-30 minutes; Preferably, the extrusion granulation is carried out in a screw extruder; Preferably, the operating temperature of the screw extruder is 100-150°C.
9. The preparation method according to claim 7 or 8, characterized in that: The working temperature of the wire extruder is 100-190°C; Preferably, the radiation cross-linking dosage is 4-10 Mrad.
10. Use of the offshore photovoltaic cable material according to any one of claims 1 to 6 in an offshore photovoltaic module.
Citation Information
Patent Citations
Chemical crosslinking polyolefin insulating rubber for offshore oil gas engineering cable and manufacturing method
CN102964668A
Offshore photovoltaic power station cable capable of ultraviolet resistance, high temperature resistance and corrosion resistance
CN106898427A
Marine photovoltaic cable sheath material and preparation method thereof
CN117777586A
Cited By
Highly reliable water-blocking double-core photovoltaic cable for offshore floating
CN121565551B